Analisis Pengukuran Kepuasan Pengguna pada Aplikasi Pesan Antar Pizza Menggunakan Metode End User Computing Satisfaction (EUCS) - Faizah, Siti; Pudji, Eni Pudji (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
User reviews of the Pizza Hut and Domino Pizza applications on the Google Play Store indicate a relatively high number of complaints, highlighting the need for an evaluation of user satisfaction levels. This study aims to measure user satisfaction and identify the factors that influence it in both applications. A quantitative research method was employed using the End User Computing Satisfaction (EUCS) model. The study population consisted of users of the Pizza Hut and Domino Pizza applications, with samples of 47 respondents for Pizza Hut and 46 respondents for Domino Pizza, selected through simple random sampling. Data analysis was conducted using PLS-SEM with SmartPLS version 4. The results show that, out of the five hypotheses tested for the Pizza Hut application, three were accepted and two were rejected. The factors that significantly influence user satisfaction include accuracy, ease of use, and format, while content and timeliness were found to have no effect. For the Domino Pizza application, three hypotheses were also accepted and two were rejected, with ease of use, format, and timeliness emerging as significant factors, whereas accuracy and content showed no influence. These findings indicate that both systems have not fully met user satisfaction. The outcomes of this research are expected to provide insights for improving system development and enhancing the service quality of the Pizza Hut and Domino Pizza applications.